PELUANG KARIR PADA PP-PAUDNI REGIONAL II SEMARANG : Faktor Yang Mempengaruhi dan Dampaknya Terhadap Komitmen Organisasional - Ngasni, 11.42.02.0037 (Students Journal of Economic and Management, 2013)
The phenomenon happened in PP-PAUDNI Regional II Semarang indicated that inferiority in career opportunity was not always followed by the lack of organizational commitment. Self esteem may influence this situation. Self esteem could be a moderation factor in the relation between career opportunity and organizational commitment. This study aimed to examine and find out factors that influence career opportunity and the impact of career opportunity on organizational commitment. A hundred respondents of PP-PAUDNI Regional II Semarang were set in this study that applied purposive sampling technique. The available technique for examining and analyzing data included validity test using factor analysis, reliability test using alpha cronbach, multiple regression analysis, t test and moderation test in testing and proving the hypothesis. Result of this study showed the career opportunity was low on the other hand organizational commitment was constantly high. The inferiority of career opportunity belonged to 3 factors namely: the fairness in maintaining career, career system as well as the carefulness of the employers to their employee. The last two factors were the influencing ones on career opportunity submission but the impact were not significant. The influence was about 0, 05. The high organizational commitment was caused by high self esteem. Self esteem was a variable which moderates the relation between career opportunity and organizational commitment. The moderation impacts had strengthen and improved the relation between career opportunity and organizational commitment. The moderation building of self esteem covered all dimension of organizational commitment, the affective, continuant and normative one. Â  Key words: career opportunity, self esteem, organizational commitment